Investigation of Potential Grounding Compound for Portable Applications - N.A.M. Hasni; R. Abd-Rahman; H. Ahmad; N.A.M. Jamail; M. S. Kamaruddin; S.S. Ridzwan (International Journal of Electrical and Computer Engineering (IJECE), 2017)
This paper applies to the electrical engineering world by making earthing system portable in providing low and acceptable resistance path. The system is develop in a small scale portable earthing system against the massiveness of Earth and becomes leverage if soil at the place is not suitable for plant grounding system. Hence, this paper presents findings on the research of new grounding medium material that will be housed in a small scale enclosure which behaves like native earth related earthing system by using kaolin and bauxite. The data obtained from lightning flashover testing, morphological and chemical composition of material analysis indicated that bauxite is more useful for portable grounding system application much better than kaolin in term of zero reference point function. The portable earthing system can be apply to air aviation systems , railway systems and military sectors particularly for electronic equipment zero referencing.